Deteksi Dini Depresi pada Ibu Postpartum - Anggarini, Inge Anggi (Khidmah, 2024)
Changes in the postpartum period require a lot of adjustments so they can cause both psychological and physical disorders. Depression in postpartum mothers tends to be invisible but has a negative impact. Mothers who cannot adapt to the critical postpartum period can experience psychological disorders. This disorder is common in women during pregnancy and postpartum but often goes undiagnosed and untreated.. Maternal depressive symptoms affect the mother's emotional and cognitive ability to interact with the baby and family, especially in conditions of long-term depression. Education or counseling can be carried out to increase knowledge or understanding of postpartum mothers. The community service method is in the form of education or counseling with the title Early Detection of Depression in Postpartum Mothers. This activity will be carried out in January-February 2024 at PMB Herasdiana Palembang. During this 2 month period, several stages of preparation were carried out and coordinated with related parties and provided education to mothers at PMB Herasdiana Palembang.